Effect of New Zealand blackcurrant extract on performance during repeated 4 km cycling time trials - Murphy, C.; Cook, M. D.; Willems, M. E. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
New Zealand blackcurrant (NZBC) extract increased 16.1 km cycling time trial performance. It was hypothesized that NZBC extract would enhance repeated 4 km time trial performance.